Study of the Kulinkovich Synthesis of 1-Methylcyclopropanol and Its Conversion into 1-Methylcyclopropyl 4-Nitrophenyl Carbonate - Wright, Stephen W.; Darout, Etzer; Stevens, Benjamin D. (Synthesis, 2013)
A detailed investigation of the preparation of 1-methylcyclopropanol via the Kulinkovich reaction is presented. Reaction and workup parameters were optimized to provide a reproducible procedure for the synthesis of multigram quantities of 1-methylcyclopropanol. Key improvements were the use of titanium tetra(2-ethyl)hexyloxide as catalyst, reduction in the volume of reaction solvent, addition of the methyl acetate starting material in portions, and azeotropic distillation to remove by-products. The preparation of the 4-nitrophenyl carbonate ester was likewise studied and optimized.
Keywords: titanium; cyclopropanes; catalysis; carbene complexes; alcohols